Banning Drugs in Sports: A Skeptical View - Fost, Norman (The Hastings Center report, 1986)
Recent proposals to punish athletes for taking drugs or to impose mandatory drug testing cannot be defended in ethical terms. Nor is it possible to distinguish consistently between ethical and unethical uses of restorative drugs, additive drugs, painkillers, and recreational drugs. We oppose drugs in sports because they violate the majority notion of acceptable behavior. But such opposition has more to do with defending the ideals of the community than with creating policies that are ethically sound